2012
DOI: 10.2131/jts.37.345
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent hyperactivity of offspring after maternal protein restriction during the second half of gestation and lactation periods in rats

Abstract: -To clarify the effect of systemic growth retardation on behavior, pregnant rats were fed a synthetic diet with either a normal (20% casein) or low (10% casein) protein concentration from gestational day 10 to postnatal day (PND) 21 at weaning. Offspring were examined for sensory and reflex functions, detailed clinical observations, manipulative test, grip strength, motor activity and water-filled multiple T-maze test. Lowering trend in the air righting reflex index during lactation period and a decrease in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Axonal density ↓ left hemispheric anxiety and memory pathways [117] Axonal degeneration + cingulate and somatosensory cortices, internal capsule, pontocerebellar tract [115] Microstructural reorganisation + [163] MYELINATION Cerebrum = [162][117] Corpus callosum = [222] ↓ d60 [40] Cingulum ↓ d60 [112] Internal and external capsule = d60 [112] Astrogliosis Hippocampus ↑CA1 [113,115] Dentate gyrus ↑ [113,115] Entorhinal cortex ↑ [113,115] Cingulum ↑ [113,115] = [94] Fornix ↑ [113] Motor cortex = [115] Somatosensory cortex ↑ [115] Neonatal neurobehaviour = reflexes [79] ↓ righting reflex, d3-4 males, d3 females [87] ↓cliff avoidance, d7 females, d8, both sexes [87] ↓negative geotaxis, d7-8 males [87] = reflexes d10-21 [165] ↓surface righting, d2-9 ↓ negative geotaxis d 4-15 [129] ↓righting reflexes, locomotion, head turning and smell test scores as d1 neonates [116] Neuromotor ↓ grip strength adult males [165] ↓ motor learning, males [129] ↓motor learning, adults [222] Spatial learning = adult males [95] = adults [97,165] = adult males [167] ↓initial simple maze tests (lambs) [122] = extended simple maze testing, obstacle course tasks, tmaze tasks (lambs) [122] ↓initial simple maze tests (male lambs and young adults) [150] Revers...…”
Section: White Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…Axonal density ↓ left hemispheric anxiety and memory pathways [117] Axonal degeneration + cingulate and somatosensory cortices, internal capsule, pontocerebellar tract [115] Microstructural reorganisation + [163] MYELINATION Cerebrum = [162][117] Corpus callosum = [222] ↓ d60 [40] Cingulum ↓ d60 [112] Internal and external capsule = d60 [112] Astrogliosis Hippocampus ↑CA1 [113,115] Dentate gyrus ↑ [113,115] Entorhinal cortex ↑ [113,115] Cingulum ↑ [113,115] = [94] Fornix ↑ [113] Motor cortex = [115] Somatosensory cortex ↑ [115] Neonatal neurobehaviour = reflexes [79] ↓ righting reflex, d3-4 males, d3 females [87] ↓cliff avoidance, d7 females, d8, both sexes [87] ↓negative geotaxis, d7-8 males [87] = reflexes d10-21 [165] ↓surface righting, d2-9 ↓ negative geotaxis d 4-15 [129] ↓righting reflexes, locomotion, head turning and smell test scores as d1 neonates [116] Neuromotor ↓ grip strength adult males [165] ↓ motor learning, males [129] ↓motor learning, adults [222] Spatial learning = adult males [95] = adults [97,165] = adult males [167] ↓initial simple maze tests (lambs) [122] = extended simple maze testing, obstacle course tasks, tmaze tasks (lambs) [122] ↓initial simple maze tests (male lambs and young adults) [150] Revers...…”
Section: White Mattermentioning
confidence: 99%
“…Behavioural anxiety = male pups [79] =/↑ adult males [93,94] ↓ adults [98,216] ↑ reactivity to physical restraint and surprise, adults [84] ↑ adolescent females = adolescent males [131] ↑ adults [117] ↑ low birth weight female lambs [150] Spontaneous ambulation = adult males [94,95] ↑ females [165] ↑ in isolation tasks, adults [84] ↑ adults [113][114][115] ↓ adult males [160] ↓ Hyperactivity ↑ adult females [165] ↑adults [113][114][115] Exploratory behaviour ↑adult females [216] ↑adults [113][114][115] ↓ adults [117,163] Response to novelty ↓novelty seeking, adults [84] = adults [113] …”
Section: Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, the study demonstrated that maternal undernutrition during pregnancy caused reduced physical activity in the offspring shortly after weaning, and this persisted to adulthood. Two subsequent studies examined variants of another rat model of gestational undernutrition, assigning pregnant dams to a normal or low-protein diet during gestation ( 37 ) or gestation through weaning ( 38 ) . In the first study, offspring of control and undernourished dams were cross-fostered at birth to control dams to limit the exposure (undernutrition) to prenatal development.…”
Section: Biological Determinants and Developmental Programming Of Phymentioning
confidence: 99%
“…Both male and female offspring of undernourished dams engaged in much less voluntary exercise than control offspring ( 37 ) . The other study of maternal low-protein diet ( 38 ) differed from the first in that the exposure started at day 10 of gestation and continued through the end of the suckling period. Rather than reduced physical activity, this study reported increased motor activity in adult (P72) offspring of undernourished dams.…”
Section: Biological Determinants and Developmental Programming Of Phymentioning
confidence: 99%